Warning regarding thrombosis‐in‐transit across the patent foramen ovale associated with pulmonary embolism: ultrasonographic imaging analysis. Issue 1 (15th April 2020) - Morinaga, Kentaro; Oda, Jun; Yamashita, Jun; Nakano, Hiroki; Ogino, Hitoshi; Takahashi, Satoshi
Abstract : Contrast‐enhanced CT is useful for diagnosing Pulmonaly embolism (PE) but not for foramen ovale thrombi. Therefore, cardiac ultrasonographic observation of the atrial septum is important to avoid overlooking foramen ovale thrombi.